2017
DOI: 10.1158/2159-8290.cd-15-1523
|View full text |Cite
|
Sign up to set email alerts
|

Activating ESR1 Mutations Differentially Affect the Efficacy of ER Antagonists

Abstract: Recent studies have identified somatic ESR1 mutations in patients with metastatic breast cancer (MBC) and found some of them to promote estrogen-independent activation of the receptor. The degree to which all recurrent mutants can drive estrogen-independent activities and reduced sensitivity to ER antagonists like fulvestrant is not established. In this report, we characterize the spectrum of ESR1 mutations from over 900 patients. ESR1 mutations were detected in 10%, with D538G being the most frequent (36%), f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

32
372
1
11

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 318 publications
(416 citation statements)
references
References 26 publications
32
372
1
11
Order By: Relevance
“…Table S9). In addition to and consistent with a recent report (33), we showed that V422del activates estrogen-independent ERα transcription approximately two-fold (Suppl. Fig.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Table S9). In addition to and consistent with a recent report (33), we showed that V422del activates estrogen-independent ERα transcription approximately two-fold (Suppl. Fig.…”
Section: Discussionsupporting
confidence: 93%
“…Importantly, these mutants have been shown to be transcriptionally active in the absence of estrogen. To date, ERα p.V422del has only been reported in a single case of endometrial cancer in the Catalogue of Somatic Mutations in Cancer (COSMIC) database (32) and most recently, by Toy, et al (33). Secondary analysis of FoundationOne™-profiled breast tumors revealed 10 additional tumors that harbor ERα V422del (Suppl.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, affinity studies showed that the LBD-mutated receptors have a decreased affinity for estradiol (E2). Finally, several studies showed co-activator binding to mutant ER in ligand-independent conditions [15,16]. Together, these observations provide a mechanistic explanation for the ligand-independent activity.…”
Section: Introductionmentioning
confidence: 66%
“…The majority of these samples were ER+ metastatic tumors, with 95 patients found to have a somatic ESR1 mutation. Not surprisingly, 85 of the 95 patients had ER+ metastatic disease [15].…”
Section: Introductionmentioning
confidence: 97%